Epidemiologic Situation of the Congenital and Maternal Syphilis in thesub Public sectorsub Public sectorsub Public sectorsub Public sectorsub Public Sector, Paraguay – 2000-2004 - Paez, Malvina; Riveros, María Isabel R (Brazilian Journal of Sexually Transmitted Diseases, 2006)
Introduction: syphilis can affect the pregnant woman and be transmited to the fetus. Approximaly two third of these pregnancies lead to cases of congenitalsyphilis or spontaneous abortion, which are complications that could de prevented with reasonable technologies of low cost. Objective: determine theEpidemiologic Situation of the maternal and congenital syphilis in the Sub Public Sector of Paraguay, during a period of five years (2000-2004). Methods:Descriptive and retrospective study. The target population was the pregnant women and the cases of congenital syphilis, registered in the Department ofBioestatistics of the Ministry of Public Health whin a period of five years (2000-2004). Results: an average of 122.442 pregnant women per year enrolled tothe prenatal consultation, 75% of these woman to the prenatal control after the fourth month of pregnancy. The diagnostic service of VDLR just covered 13%of pregnant woman. The rate of pregnant woman with syphilis was 5,85%, the most affected group had avarge age ranging fron 20 to 39 years old. A total of1,173 cases of congenital syphilis was registered, with a coefficient of 2.7 x 1000 births; 95% with less than one year. Conclusion: maternal and congenitalsyphilis were registered in all the sanitary regions of the country, with greater prevalence and incidence in the border cities. Maternal syphilis was high butstable (5,8%), where as congenital syphilis was in frank increase. The health services had a low cover age in VDRL diagnosis of pregnant women. Our resultssuggest that it is important to implent strategies that help modifying this situation.